Urban violence in the Middle East changing cityscapes in the transition from empire to nation state (Space and place, 2015)
"Covering a period from the late eighteenth century to today, this volume explores the phenomenon of urban violence in order to unveil general developments and historical specificities in a variety of Middle Eastern contexts. By situating incidents in particular processes and conflicts, the case studies seek to counter notions of a violent Middle East in order to foster a new understanding of violence beyond that of a meaningless and destructive social and political act. Contributions explore processes sparked by the transition from empires--Ottoman and Qajar, but also European--to the formation of nation states, and the resulting changes in cityscapes throughout the region"--Provided by publisher